E-maintenance at the syariah court: its effectiveness in helping single mothers in Malaysia - Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Mohd Zin, Najibah (2014)
E-Maintenance introduced by the Syariah Court of Malaysia is the only system of its kind available in the Muslims countries. The special feature of this system is its ability to monitor data and history of maintenance order granted by the Syariah Court. Under this system of e-maintenance, every maintenance order granted by the Syariah Court will be entered into the system to enable officials of Family Support Division (BSK) to take pro-active step by contacting the wife to find out whether or not her former husband has complied with the maintenance order issued by the Syariah Court. If BSK staff discovers that ex-husband fails to pay nafkah as ordered by the Court, then the parties will be required to undergo mediation process. The objective of this mediation process is to find out causes of failure of such payment by the husband. For the year 2010, 58% of 852 cases were successfully resolved through mediation throughout Malaysia. However, if the husband still refuses to pay nafkah after mediation sessions end, then the officer will file enforcement actions against the former husband/father in the Syariah Court. There are some form of enforcements that can be carried out by officers of the BSK such as judgment debtor summons, seizure and sale, and Hiwalah.